Improving global integration of crop research - Reynolds, Matthew P.; Braun, Hans-Joachim; Cavalieri, Anthony J.; Chapotin, Saharah; Davies, William; Rosegrant, Mark W.; Quilligan, Emma (American Association for the Advancement of Science, 2017)
In recent decades, the scientific, development, and farm communities have contributed to substantial gains in crop productivity, including in many less developed countries (LDCs), yet current yield trends and agri-food systems are inadequate to match projected demand. Addressing transnational crop challenges will require refinement of research infrastructure and better leverage of global expertise and technologies. Drawing on lessons learned from international collaboration in wheat, we outline how such a model could evolve into a Global Crop Improvement Network (GCIN) encompassing most staple food crops, providing access to well-controlled “field laboratories,” while harmonizing research practices and sharing data. Combined with socioeconomic and cropping systems research, a GCIN could revolutionize the ability to understand and model crop responses to environments globally and accelerate adoption of vital technologies.